Maximizing the weighted number of just‐in‐time jobs in a distributed flow‐shop scheduling system - Shabtay, Dvir (Naval research logistics, 2023)
We study a set of scheduling problems in a distributed flow‐shop scheduling system consisting of several flow‐shop production systems (factories) working in parallel. Our objective is to assign the jobs to the factories, and to devise a job schedule for each of the factories such that the weighted number of jobs completed in just‐in‐time mode is maximized. We classify computational complexity of the problems, including the special cases of unit weights and job‐ or machine‐independent processing times.